(untitled) (The Review of Diabetic Studies, 2025)
Substance use disorders and personality disorders are increasingly encountered in acute medical and surgical settings, where they significantly complicate clinical decision-making, perioperative safety, staff–patient interactions, and postoperative outcomes. Patients with addiction or maladaptive personality traits frequently present with pain management challenges, behavioral dysregulation, nonadherence, and heightened risk of perioperative complications. Traditional biomedical models are insufficient to address these complexities, necessitating a coordinated multidisciplinary approach. This review examines the collaborative roles of clinical psychologists, nurses, and operating room technicians in managing addiction and personality disorders within acute and surgical environments. Emphasis is placed on behavioral assessment, risk stratification, perioperative communication, de-escalation strategies, infection control, and staff safety. By integrating psychological expertise, nursing continuity, and operating room workflow adaptation, this review proposes a pragmatic framework to enhance patient outcomes, reduce adverse events, and improve healthcare worker resilience in high-stress clinical settings.